Anrukinzumab, an anti-interleukin 13 monoclonal antibody, in active UC: efficacy and safety from a phase IIa randomised multicentre study. Issue 6 (7th January 2015) - Reinisch, Walter; Panés, Julián; Khurana, Sunil; Toth, Gabor; Hua, Fei; Comer, Gail M; Hinz, Michelle; Page, Karen; O'Toole, Margot; Moorehead, Tara McDonnell; Zhu, Hua; Sun, YanHui; et al.
Abstract : Objective: Interleukin 13 (IL-13) is thought to play a key role as an effector cytokine in UC. Anrukinzumab, a humanised antibody that inhibits human IL-13, was evaluated for the treatment of UC. Design: In a multicentre, randomised, double-blind, placebo-controlled study, patients with active UC (Mayo score ≥4 and <10) were randomised to anrukinzumab 200, 400 or 600 mg or placebo. Patients received five intravenous administrations over 14 weeks. The primary endpoint was fold change from baseline in faecal calprotectin (FC) at Week 14. Secondary endpoints included safety, pharmacokinetics and IL-13 levels. Results: The modified intention-to-treat population included 84 patients (21 patients/arm). Fold change of FC from baseline at Week 14 was not significantly different for any treatment groups compared with the placebo. The study had a high dropout rate, in part, related to lack of efficacy. The exploratory comparisons of each dose were not significantly different from placebo in terms of change from baseline in total Mayo score, clinical response, clinical remission and proportion of subjects with mucosal healing. An increase in serum total IL-13 (free and bound to anrukinzumab) was observed for all anrukinzumab groups but not with placebo. This suggests significant binding of anrukinzumab to IL-13. The safety profile was not different between the anrukinzumab and placebo groups. Conclusions: A statistically significant therapeutic effect of anrukinzumab could not be demonstrated in patients with active UC in spite of binding of anrukinzumab to IL-13. Trial registration number: ClinicalTrials.gov number NCT01284062 .